Single‐Stage Frozen Elephant Trunk Reconstruction in Complex Disease of the Aortic Arch with Aberrant Right Subclavian Artery. Issue 2 (25th November 2013) - Leone, Alessandro; Pantaleo, Antonio; Pacini, Davide; Di Marco, Luca; Di Bartolomeo, Roberto
Abstract Aberrant right subclavian artery (ARSA) is the most common anomaly of the aortic arch. We describe two cases of patients affected by complex lesions of the aortic arch with the ARSA, both treated with the frozen elephant trunk technique and reconstruction of the ARSA. doi: 10.1111/jocs.12257 (J Card Surg 2014;29:234–237)